Fentanyl as a premedication for anaesthesia in paediatric surgery (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v19i1.3848Journal of Chittagong Medical College Teachers' Association 2008: 19(1):23-27